2013
DOI: 10.1088/0031-9155/58/16/5735
|View full text |Cite
|
Sign up to set email alerts
|

A fast referenceless PRFS-based MR thermometry by phase finite difference

Abstract: Proton resonance frequency shift-based MR thermometry is a promising temperature monitoring approach for thermotherapy but its accuracy is vulnerable to inter-scan motion. Model-based referenceless thermometry has been proposed to address this problem but phase unwrapping is usually needed before the model fitting process. In this paper, a referenceless MR thermometry method using phase finite difference that avoids the time consuming phase unwrapping procedure is proposed. Unlike the previously proposed phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Temperature uncertainty for ex vivo porcine liver experiments in this study (1.49 °C) maintained an accuracy similar to the results reported by Harth et al on a 1.5 T MRI scanner (1.50 °C) [ 41 ]. Human brain studies showed that the temperature error obtained by the phase-drift correction PRFS thermometry was larger than that calculated by the phase gradient method, and smaller than that obtained by the phase finite difference model from a previous study [ 40 ]. The distinction of results could be acceptable and reasonable due to the obvious difference in field strengths.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Temperature uncertainty for ex vivo porcine liver experiments in this study (1.49 °C) maintained an accuracy similar to the results reported by Harth et al on a 1.5 T MRI scanner (1.50 °C) [ 41 ]. Human brain studies showed that the temperature error obtained by the phase-drift correction PRFS thermometry was larger than that calculated by the phase gradient method, and smaller than that obtained by the phase finite difference model from a previous study [ 40 ]. The distinction of results could be acceptable and reasonable due to the obvious difference in field strengths.…”
Section: Discussionmentioning
confidence: 69%
“…Images were scanned by GRE sequence in the transverse plane using the following scanning parameters: TR/TE = 50/30 ms, FA = 30°, Matrix size = 128 × 128, FOV = 256 mm, number of slices = 3, ST/SG = 8/0 mm, acquisition time = 6.4 s/slice. In order to compare with the results obtained by Zou et al at 3.0 T MR scanner [ 40 ], the width of the selected inner and outer ROI (see as Fig. 3 b) were both 10 pixels (2 cm), which was the same as the above published literature.…”
Section: Methodsmentioning
confidence: 99%
“…Further improvements are offered by reference-less methods [126,153], whereby a background phase is derived from the n th image during ablation. This is achieved by fitting a polynomial to the surrounding unheated region and extrapolating to the heated region, thus avoiding subtraction with a separate image [21,154]. This approach is only successful if sufficient SNR is available, and if water-fat interfaces which can lead to inaccurate polynomial fitting are absent.…”
Section: Limitations In Methods Based On the Chemical Shift Of Water mentioning
confidence: 99%
“…The main drawback of PRF, especially in in vivo applications [14], is its high sensitivity to motion. Although recently many authors are investigating several promising strategies to reduce artifact due to patient movements [17,18], the effective spread of PRF is still limited in clinical applications. For the above mentioned reasons, our experiments employed the thermal dependence of T 1 of tissue for the estimation of temperature distribution within pancreas and liver during LA.…”
Section: Monitoring Of Tissue Temperature Through T 1 -Weighted Imagesmentioning
confidence: 99%